2020
DOI: 10.3389/fcimb.2020.00279
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antigen Presentation by Deletion of Viral Immune Evasion Genes Prevents Lethal Cytomegalovirus Disease in Minor Histocompatibility Antigen-Mismatched Hematopoietic Cell Transplantation

Abstract: Hematoablative treatment followed by hematopoietic cell transplantation (HCT) for reconstituting the co-ablated immune system is a therapeutic option to cure aggressive forms of hematopoietic malignancies. In cases of family donors or unrelated donors, immunogenetic mismatches in major histocompatibility complex (MHC) and/or minor histocompatibility (minor-H) loci are unavoidable and bear a risk of graft-vs.-host reaction and disease (GvHR/D). Transient immunodeficiency inherent to the HCT protocol favors a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…This advantage, however, might also be seen as a limitation, because mismatch by gene deletion has no obvious correlate in clinical HCT. As we show in an alternative model of GvH-HCT with a donor (C57BL/6; H-2 b ) vs. recipient (BALB.B; H-2 b ) match in MHC antigens but mismatch in minor histocompatibility antigens (minor-HAg), GvH-associated lethality of mCMV infection and its prevention by enhanced viral antigen presentation can be reproduced (Gezinir et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…This advantage, however, might also be seen as a limitation, because mismatch by gene deletion has no obvious correlate in clinical HCT. As we show in an alternative model of GvH-HCT with a donor (C57BL/6; H-2 b ) vs. recipient (BALB.B; H-2 b ) match in MHC antigens but mismatch in minor histocompatibility antigens (minor-HAg), GvH-associated lethality of mCMV infection and its prevention by enhanced viral antigen presentation can be reproduced (Gezinir et al, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…For quite some time, this correct finding was mistaken as an evidence against an in vivo relevance of immune evasion in general, although soon thereafter a crucial role of immune evasion in the effector phase of the antiviral CD8 + T-cell response was demonstrated in many models (for a review, see (104)). Recently, it has been shown that immune evasion is the reason for a failure in preventing lethal virus spread and histopathology in mouse models of allogeneic HCT and CMV infection (105,106).…”
Section: Collins-mcmillen and Goodrum To Propose An Equilibriummentioning
confidence: 99%
“…Deletion of Rat CMV R33 reduced vascular sclerosis and increased time to chronic rejection in a rat model of heart transplantation, and deletion of MCMV M33 reduced cardiac allograft vasculopathy in a mouse model of aortic transplantation (Streblow et al, 2005;Fritz et al, 2018). These animal models continue to be developed, including the generation of a humanized mice model, which may soon lead to further exciting insight about the roles of individual viral genes in post-transplant cytomegalovirus disease (Streblow et al, 2015;Crawford et al, 2020;Gezinir et al, 2020;Holtappels et al, 2020;Shah et al, 2020). However, the species-specific nature of herpesviruses will continue to create challenges in understanding how vGPCRs function in vivo.…”
Section: Post-transplant Diseasementioning
confidence: 99%